Use of intracage ventilation systems in animal facilities - Carissimi, André Silva; Teixeira, Maria Araújo; Chaguri, Luziane do Carmo Andrade Guinski; Merusse, José Luiz Bernardino (Acta Scientiae Veterinariae, 2018)
The breeding and housing of animal species in intensive production systems require a higher control of the environmental variables inside the facilities, on behalf of an atmosphere that maintains a sanitary status and also promotes the well-being of the animals. The husbandry of laboratory animals is one of those productive systems in which the environmental control should be quite rigorous due to the maintenance of defined animals such as specific pathogen-free and gnotobiotics. For a long period, the control of ventilation and environmental factors of conventional animal facilities was achieved by using thermodynamic principles used for human comfort. However, in the last decades, new approaches to solve the environmental problem in animal rooms were studied, and the ventilation systems developed with base in forced convection of the air were the ones that presented the best results until the present time. Thus, this review presents, in an historical perspective, the evolution of alternative devices for caging of laboratory animals and their effects on the animals.